Analysis of Ambient Air Quality Due to Motor Vehicle Emissions Using System Dynamics Modeling on Jalan Kaliurang, Yogyakarta - Yusuf Wiryawan; Radjali Amin (PT Keberlanjutan Strategis Indonesia, 2026)
The growth of motor vehicles in the Special Region of Yogyakarta has contributed to increased vehicle exhaust emissions, particularly carbon monoxide (CO), which has the potential to reduce ambient air quality and endanger public health. This study aims to analyze traffic density, ambient air quality based on CO parameters, projected traffic volume and emission loads over the next ten years, and to formulate environmental management strategies for the Jalan Kaliurang segment from STA 0+000 to STA 1+330. The study was conducted through direct air quality measurements using a minivol air sampler and traffic volume counts involving motorcycles, passenger cars, buses, and trucks. The data were analyzed using a system dynamics approach and visualized through CO distribution mapping. The results showed that traffic volume reached 3,948 units/2 hours in the morning and 5,633 units/2 hours in the afternoon. The measured CO concentration ranged from 341.03 to 632.14 µg/m³, with a very high concentration distribution identified at a distance of 0.094 km. Based on system dynamics modeling, traffic density is projected to reach 17,158 passenger car units/day, with an emission load of 564,827 grams/day. The recommended management strategies include increasing roadside vegetation, implementing vehicle emission testing, promoting smart driving practices, and evaluating the obligation to conduct traffic impact analysis.